2014
DOI: 10.1590/s0102-86502014001300001
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 on induced osteogenic differentiation of human dermal fibroblast

Abstract: PURPOSE:To evaluate the role of transforming growth factor beta 1 (TGF-β1) on the induced osteogenic differentiation of human dermal fibroblasts. METHODS:We performed four groups with cultured dermal fibroblasts according to the culture medium: CONTROL (DMEM culture medium); TGF-β1 (DMEM culture medium with 10 ng/ml of TGF-β1); OSTEOG (DMEM culture medium with 0.5 µg/ml of ascorbic acid, 10 mmol/l of β-glycerophosphate and 10 nmol/L of dexamethasone); and OSTEOG/TGF-β1 (osteogenic medium with 10 ng/ml of TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Interestingly, the stimulation of osteoblastogenesis by ALK5 inhibition is the opposite of what we observed in our study with the different ALK5 inhibitor GW788388 (13). In another study, the addition of TGF-β to osteogenic media was shown to improve the capacity of dermal fibroblasts for osteogenic transdifferentiation, although it did not contribute to mineralization (18). These differences may be attributed to the different growth factor compositions between these models, as well as to the different properties of the chemical inhibitors; for example, GW788388 is known to additionally target ALK4 and ALK7, which are TGF-β type I receptors for activin signaling (59).…”
Section: Transgene Free-mediated Osteogenic Transdifferentiationcontrasting
confidence: 95%
“…Interestingly, the stimulation of osteoblastogenesis by ALK5 inhibition is the opposite of what we observed in our study with the different ALK5 inhibitor GW788388 (13). In another study, the addition of TGF-β to osteogenic media was shown to improve the capacity of dermal fibroblasts for osteogenic transdifferentiation, although it did not contribute to mineralization (18). These differences may be attributed to the different growth factor compositions between these models, as well as to the different properties of the chemical inhibitors; for example, GW788388 is known to additionally target ALK4 and ALK7, which are TGF-β type I receptors for activin signaling (59).…”
Section: Transgene Free-mediated Osteogenic Transdifferentiationcontrasting
confidence: 95%
“…In another approach, the subcutaneous ectopic bone formation in mice after implantation of the epigenetically modified fibroblasts [ 10 ]. Further, differentiation of fibroblasts toward the osteoblast lineage was also demonstrated with treatment of osteoclast-conditioned media, and TGF-β was shown to improve the capacity of fibroblasts for osteogenic differentiation [ 11 , 12 ]. The similarities of fibroblasts and mesenchymal stem cells support the use of fibroblasts as an appropriate cell type to study osteogenesis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…TGF‐β1 contradictorily affects osteogenesis; while some researchers have shown that TGF‐β1 induces osteogenesis, either alone or together with other members of the family, such as BMP, in vivo and in vitro, others showed that TGF‐β1 had inhibitory effects on osteogenic markers such as alkaline phosphatase in mesenchymal stem cells . The variable effects of TGF‐β1 on osteogenesis appear to be dose or stage dependent .…”
Section: Discussionmentioning
confidence: 99%